PERSEPSI GURU TERHADAP MODEL KEPEMIMPINAN KEPALA SEKOLAH MENENGAH KEJURUAN NEGERI (SMKN) 2 KUPANG MENURUT KERANGKA SERVANT LEADERSHIP - , Jevri Yohanes Cornelis Bolla ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this study was to identify the perceptions of teachers to be the principal leadership model of servant leadership framework of this research is descriptive quantitative method and sample in this study is the teacher of SMK Negeri 2 Kupang Kupang in East Nusa Tenggara Province. The research instrument used to collect the data of this study is distributing questionnaires to SMKN 2 Kupang teachers . Servant leadership model used in this study is based on the five dimensions of research results by Barbuto and Wheeler (2006) and the conceptual framework for measuring servant leadership proposed by Wong and Page (2003) and equipped with demographic questions. Leadership of SMK Negeri 2 Kupang viewed from the framework of servant leadership in categorized as high All dimensions of emotional healing, wisdom, persuasive mapping, organizational stewardship, service vision and humility are perceived as high in cumulative average of 106.89 or 76.35%.Six demographic aspects used in assessing eight dimensions of servant leadership in this study, only two aspects, namely, certification status and education level were significant while the other four aspects, namely employment status, gender, certification, and aspects of the working period has no significant effect.